OS 23-02 THE ROLE OF COMPLEMENT C5a-MEDIATED PLACENTAL DYSFUNCTION IN THE ONSET OF PREECLAMPSIA. (September 2016) - Ma, Yu; Ruan, Cheng-Chao; Zhang, Yu; Ge, Qian; Wu, Qi-Hong; Kong, Ling-Ran; Gao, Ping-Jin
Abstract : Objective: Women with preeclampsia (PE) display excessive activation of complement system. However, little is known about the detailed cellular and molecular mechanism of complement activation in the development of PE. Here, we hypothesized that whether complement C5a contributes to the onset of PE through its effect on trophoblasts. Design and Method: In this study, 23 women with established PE and 32 normotensive women were recruited. At entry, peripheral and central blood pressure and pulse wave velocity (PWV) were performed. Immunofluorescence and quantitative real-time PCR were performed to identify the expression of C5a in the placenta. Transwell and matrigel assay was conducted to assess the effect of C5a on invasion and angiogenesis of human trophoblast cell lines. The serum level of C5a was measured by ELISA. Results: We detected an elevated C5a deposition in the placenta of patients with PE and C5aR was found highly expressed in syncytiotrophoblasts. In cultured trophoblast cell lines, C5aR agonist peptide inhibited the migration and angiogenesis of trophoblasts. C5aR agonist peptide stimulation also resulted in increased anti-angiogenic factors but decreased pro-angiogenic factors. In maternal circulation, the concentration of C5a was higher in women with PE compared to normotensive women (99.75 ± 29.27 ng/ml vs 76.35 ± 16.97 ng/ml mean ± SD P < 0.01). And meanwhile C5a has positive correlation with systolic blood pressure ( r = 0.371, P < 0.01) and diastolic blood pressure ( r = 0.343, P < 0.05). Women with PE displayed poor arterial function, which was also positively correlated with C5a level. Conclusions: Our data suggest that C5a contributed to the dysfunction of placenta by inhibition of migration and angiogenesis of trophoblast cells via C5aR in parallel with increase of blood pressure and arterial stiffness. The results indicate that C5a may have a novel role as a mediator of pathogenesis of PE, which could potentially result in gestational vascular dysfunction.